EVALUATING THE ADOPTION OF SMART SAFETY TECHNOLOGIES IN NIGERIAN CONSTRUCTION INDUSTRY: CHALLENGES AND BENEFITS - Augustine Chibueze Iherobiem (Universitas Nusa Cendana, 2025)
This study investigates how smart safety technologies are being adopted in Nigeria's construction sector. The study used a quantitative methodology using a survey questionnaire to collect data from Nigerian construction industry professionals. The study's target group consisted of construction professionals who lived in Ogun State, Nigeria's Ijebu Ode Area. The researcher selected a sample size of 150. The exploratory factor analysis and principal component analysis extraction procedures were used to analyse the data. The study came to the conclusion that the application of smart safety technology in Nigeria's construction sector has improved project completion and success while lowering accidents and injuries. Thus, the study suggested that construction companies should increase the amount of money allocated to purchase new technologies and offer frequent training programs to teach their employees how to use them in order to help overcome the fundamental barriers that prevent the adoption of smart safety technology. Keywords: Construction Safety; Smart Safety Technologies; Project Management